"Us and them”- a disengaged community of stakeholders. An assessment of council and community relations in ensuring good urban governance. A case of Bulawayo City Council. - Nyathi, Busani M. (Midlands State University, 2017)
Over the years due to a myriad of factors inter alia the lack of adequate funds and workforce capability constraints, the phenomenon of down spiraling service provision standards has continuously baffled urban local authorities. Although these components highly depict the nature of local government in Zimbabwe, the relationship between the urban local authorities and their local community of residents has been less appreciated as a valuable dogma for enhanced service provision. As such local authority and resident community relations had suffered from a series of non-collaborative efforts. Amidst such theorems of concern the study sought to assess the relationship between the City of Bulawayo and its resident communities in light of the “Us and Them” division as a phenomenon which depicted a disengaged community of stakeholders. The lack of social responsibility, lack of community interest to participate in Council organized programs, the failure to pay Council rates and rent, and the need to measure the level and extent of the “Us and Them” dichotomy were the core instigating factors behind the study. Henceforth the study explored and assessed the relationship between Bulawayo City Council and its community of residents by means of examining the roles and responsibilities of both Council and communities in ensuring good urban governance, measuring the level of civic responsibility and common purpose between the communities and Council, evaluating the extent of the “Us and Them” dichotomy between the Council and its community of residents, assessing the level of public participation in local governance issues and most importantly determining ways of harnessing the relationship between Council and its community of residents as a means of galvanizing service provision. The phenomenon of Community engagement was greatly explored indepth and most importantly the evolvement and classification of the “Us and Them” dichotomy as a social structure and its impact on local governance. The study from a population sample of 10 wards out of a total of 29 and through purposively selected personnel gathered data through interviews, questionnaires and observations and concluded that a tenuous relationship between the Council and its residents existed within Bulawayo. As a study that was anchored on qualitative research, varying reasons for the disengagement were all added up to poor service provision, lack of adequate information dissemination tools and the politicization of Council organized public forums. The study recommended valuable antidotes to the feeble Council and Community relationship, by means of galvanizing community engagement through a workable community engagement model to ensure sustainable and collaborative service provision.